URGENSI SOCIAL SKILL DAN LEADERSHIP SKILL DALAM PERSPEKTIF PEDAGOGI - I Putu Suardipa (Maha Widya Bhuwana: Jurnal Pendidikan, Agama dan Budaya, 2021)
Leadership in the realm of social skills as a science and art influences people or groups to act as expected to achieve goals effectively and efficiently. Leadership skills education is one of the important things to apply in madrasah as an organized group to achieve educational learning objectives. Social skills are the ability that a person has to dare to act and speak, express every feeling or problem faced while finding a solutive solution of his own thinking. There are 6 important results of having social skills, namely: (1) personality and identity development, (2) developing work ability, productivity, and career success, (3) improving quality of life, (4) improving physical health, (5) improving psychological health, and (6) overcoming stress. Urgency in the organization order as a form of social skills also requires. Leadership skills are the key to organizational success, as an organization, education also requires leadership aspects. Leadership skills are needed to bring constructive changes in teaching programs in accordance with the various values and objectives of decision makers. The quality of education will be at stake through that learning process. Meanwhile, the quality of learning involves conditioning both teacher professionalism, educational leadership influences organized group activities in an effort to determine the educational goals to be achieved, namely shaping people into complete human mental and social physical eye.